KARAKTERISTIK PETANI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI BAWANG MERAH (Studi Kasus di Desa Senden Kecamatan Selo Kabupaten Boyolali) - Mahananto; Agung Prasetyo; Kusriani Prasetyowati (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
Central Java was the largest shallot producing province in Indonesia with the Boyolali Regency as one of the main producers. Selo sub-district was the main contributor to organic shallot production in Boyolali Regency. This study aimed to determine the characteristics of farmers who cultivate organic shallots and to determine the production factors that affect the yield of shallots in the Argoayuningtani Farmer Group. The data used in this research are primary data and secondary data. Sampling was done by using the census method and the data analysis method used was multiple linear regression analysis. The results showed that the respondent farmers were generally young people and had a good enough education to develop organic agriculture. Production factors in the form of labor and biological pesticides have a significant effect on the yield of shallots. Variables of seeds, manure, and the land area had no significant effect on onion production. Further guidance needs to be carried out and developed because generally, farmers who work and join farmer groups are young and educated farmers, making it easier to develop organic agriculture in Boyolali Regency. Training is needed to make organic fertilizers and biological pesticides with active microbial ingredients that have been tested to increase shallot production.